Increasing Trends of Polypharmacy and Potentially Inappropriate Medication Use in Older Lung Cancer Patients in China: A Repeated Cross-Sectional Study - Tian, Fangyuan; Chen, Zhaoyan; Chen, Xi; Zhao, Mengnan (Frontiers in Pharmacology, 2022)
Objectives: Polypharmacy and potentially inappropriate medication (PIM) use are frequent in older lung cancer patients. This study aimed to examine the trends of polypharmacy and PIM use and explore risk factors for PIM use based on the 2019 Beers criteria in older Chinese lung cancer outpatients with multimorbidity. Methods: A repeated cross-sectional study was conducted using electronic medical data consisting of the prescriptions of older lung cancer outpatients in China from January 2016 to December 2018. Polypharmacy was defined as the use of five or more medications. The 2019 Beers criteria were used to evaluate the PIM use of older cancer outpatients (age ≥65 years), and multivariate logistic regression was used to identify the risk factors for PIM use. Results: A total of 3,286 older lung cancer outpatients and their prescriptions were included in the study. The prevalence of polypharmacy was 14.27% in 2016, 16.55% in 2017, and 18.04% in 2018. The prevalence of PIM use, according to the 2019 Beers criteria, was 31.94% in 2016, 35.78% in 2017, and 42.67% in 2018. The two most frequently used PIMs in older lung cancer outpatients were estazolam and tramadol. The logistic regression demonstrated that age 75 to 79, polypharmacy, irrational use of drugs, and lung cancer accompanied by sleep disorders, anxiety or depression, or pain were positively associated with PIM use in older lung cancer outpatients. Conclusion: The prevalence of polypharmacy and PIM use in older lung cancer outpatients with multimorbidity was high in China, and polypharmacy and PIM use increased over time. Further research on interventions rationing PIM use in the older lung cancer patient population is needed.